(x+3i)(x+3i)=2yi

Simple and best practice solution for (x+3i)(x+3i)=2yi equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x+3i)(x+3i)=2yi equation:


Simplifying
(x + 3i)(x + 3i) = 2yi

Reorder the terms:
(3i + x)(x + 3i) = 2yi

Reorder the terms:
(3i + x)(3i + x) = 2yi

Multiply (3i + x) * (3i + x)
(3i * (3i + x) + x(3i + x)) = 2yi
((3i * 3i + x * 3i) + x(3i + x)) = 2yi

Reorder the terms:
((3ix + 9i2) + x(3i + x)) = 2yi
((3ix + 9i2) + x(3i + x)) = 2yi
(3ix + 9i2 + (3i * x + x * x)) = 2yi
(3ix + 9i2 + (3ix + x2)) = 2yi

Reorder the terms:
(3ix + 3ix + 9i2 + x2) = 2yi

Combine like terms: 3ix + 3ix = 6ix
(6ix + 9i2 + x2) = 2yi

Solving
6ix + 9i2 + x2 = 2iy

Solving for variable 'i'.

Reorder the terms:
6ix + -2iy + 9i2 + x2 = 2iy + -2iy

Combine like terms: 2iy + -2iy = 0
6ix + -2iy + 9i2 + x2 = 0

The solution to this equation could not be determined.

See similar equations:

| 3(2x+1)-4x=2x+3 | | -3=8+4x | | 7x+8y-9=0 | | 3x-6.3=7.5 | | 8(x-5)=4x-4 | | 9+7*2= | | .666x+6=.5x+.25x | | 3x-8=-3x+28 | | 4x-7y+5=0 | | 2x+24=0 | | 3n^2-10n+4=0 | | r=2(3.14)sh | | 9m+(-5m)= | | -6x+16=16 | | 7x^2-45x-343=0 | | 3y-10+y+28=5y+20-3y | | 6x+3x=x+14 | | m=3(1,6) | | 8x^2-59x+40=0 | | 14x^2+7x+14=0 | | 8(w-3)=16 | | |-3|-|2-17|= | | n+n+1+n+2+n+3=s | | 16-(5m+8)=5+2M-11 | | |11-2|-|3-1|= | | 6(w-2)=36 | | 70.56h=3.14 | | -12x-17=67 | | 1+5y=3 | | 120/10560= | | 4(2v+4)=170 | | 360=(4x-4)(3x+3) |

Equations solver categories